Anal atresia as the diagnostic clue in VACTERL association: A first‐trimester case report. Issue 10 (8th August 2021) - Wang, Yu; Dai, Xiaohui; Liu, Hanmin; Li, Yiping; Li, Lei; Chen, Jiao
Abstract: Anal atresia is the most common malformation occurring in VACTERL association, but it is difficult to diagnose antenatally. We herein present a case of fetal anal atresia in VACTERL association diagnosed by ultrasonography and supported by autopsy. This case emphasizes the clues to ultrasonographic diagnosis of anal atresia at 11–13 +6 weeks of gestation, promoting increased awareness of VACTERL association during first‐trimester screening.